A Catholic-Indigenous Spiritual Dialogue, on Religious Experience and Creation; Toward Understanding a Text of Theology from another Culture, Through Cultural Exploration and Conversion(s) - Robson, Paul (Université Saint-Paul / Saint Paul University, 2018)
The first paper discusses interreligious dialogue, and presents a dialogue between the Catholic and Indigenous traditions. The dialogue is on the topic of religious experience and creation. The second paper inquires into what Indigenous theology might look like, and presents an example of such a work of theology. There is an exploration of the question of how someone from one culture might understand such a text, written by someone of another culture.
Keywords: Interreligious dialogue; Contextual theology